Arousing readers’ interest: an inquiry into Chinese argumentative essays - Miin, Jason Hwa Lim; Vui, Lin Chung (2021)
Arousing readers’ interest constitutes a major component in argumentative essays, but how writers use language resources to capture readers’ interest in the written discourse remains a fascinating area for a qualitative exploration. Based on a genre-based analytical framework, the researchers studied the salient linguistic resources used by professional writers to attract readers’ attention to their argumentative essays. Additional information was elicited from specialist informants to examine the circumstances under which the rhetorical move was used. It was found that writers arouse readers’ interest using five different strategies aimed at highlighting recent unusual situations, underscoring current relevance of alarming situations, reporting attention-grabbing observations, indicating rapid changes in the modern era, and foregrounding the severity of the problems encountered. Apart from identifying writers’ appeals in the five communicative functions, the researchers ascertained how writers vividly depict situations using a range of salient language resources, particularly temporal adverbials signalling noteworthy situations during previous time periods, noun phrases accentuating the significance of specific circumstances, and adjectival modifiers highlighting abundance or prevalence. Aside from illustrating how writers deploy four-character idiomatic expressions indicating deteriorating situations and rapid social transformations, this paper will reveal how writers capture readers’ attention by using adjectival phrases denoting the severity of situations, verb phrases signalling undesirable behaviours, and predicator-object structures denoting annoying habits. Recommendations are given on how instructors can use a broad array of rhetorical strategies and language resources to design exercises aimed at helping learners to aptly attract readers’ attention to their argumentative essays.